Psychoanalitic approach to politics and the discourse of capitalism - Sergio Kelman, Mario (2015)
The goal of this text is to produce a psychoanalytic approach to political discourse and the discourse of capitalism; to formalize the problems that affect the subjectivity of our time. The argumentative method is used to reach the results and the conclusions for the report of the annual period. We distinguish the political scene of the real political, shown at the event. Every political system is defined by the way of the sacred that is proper. The classic political discourse suffers a crisis and is replaced by the discourse of capitalism, producing new effects on subjectivity and the social field.